Metabolic polymorphism affecting DNA binding and excretion of carcinogens in humans - Bartsch, Helmut; Rojas, Margarita; Alexandrov, Kroum; Camus, A.-M.; Castegnaro, M.; Malaveille, C.; Anttila, S.; Husgafvel-Pursiainen, K.; Hietanen, E.; Vainio, H. (Pharmacogenetics and genomics, 1995)
A case-control study on lung cancer patients demonstrated the pronounced effect of tobacco smoke on pulmonary carcinogen metabolism and suggested the existence of a metabolic phenotype at higher risk for tobacco-associated lung cancer. Lung cancer patients who were recent smokers showed in their lungs (i) significantly induced CYP1A1-related enzyme activity vs smoking non-lung cancer patients; (ii) increased benzo(a)pyrene (BP) tetrol formation from BP 7,8-diol by lung microsomes; and (iii) high levels of cytochrome P4501al by immunohistochemical staining. Levels of bulky aromatic DNA adducts (by 32 P-postlabelling) and of BP-diol-epoxide (BPDE) adducts (by HPCL/fluorometry) were quantified in lung parenchyma. Aryl hydrocarbon hydroxylase activity and the level of BPDE-DNA adducts (r=0.91; p<0.001) and to a lesser degree bulky DNA adducts were correlated. Thus pulmonary CYP1A1 expression (inducibility) controls in part polycyclic aromatic hydrocarbon- DNA adduct formation in tobacco smokers and, therefore, appears to be associated with lung cancer risk. High risk subjects for lung cancer among smokers may be identifiable through genotyping for polymorphic drug metabolizing enzymes in combination with molecular dosimetry of carcinogen-DNA adducts and mutation analysis in target (surrogate) cells. Such studies in a Finnish cohort of lung cancer patients and controls are in progress. Interim results of the effect of metabolic polymorphism on the level of PAH-DNA adducts and on the excretion of mutagens in urine are summarized.